Simultaneous Temperature and Strain Sensing With Hybrid Resonator of Fiber Bragg Grating and Whispering Gallery Resonator - Lee, Aram; Lee, Seoung-Ki; Lee, Sang Hyun (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2020)
This study proposes a hybrid resonance structure of fiber Bragg grating (FBG) and whispering gallery resonator (WGR) in a single optical fiber to simultaneously measure temperature and strain. Bragg grating written in the fiber itself provides the first sensing signal in conjunction with the second signal produced by a whispering gallery mode (WGM) propagating along the circumferential cross-section of the FBG. Under changes in temperature and strain, variation in the refractive index or diameter (or length) of the fiber occurs, which also shifts the resonance frequency of each structure. Taking advantage of the difference in thermo- and strain-optic coefficients of FBG and WGR, such an integration of two different sensing techniques at an identical spot thus provides a $2\,\,{× }\,\,2$ matrix to the characteristic equation of temperature-strain sensing that realizes a cross-sensitivity-free sensing with high accuracy. An uncertainty of +/- 1.91 degrees C and $± 36.2{μ ε }$ was achieved in the experimental verification.